1986
DOI: 10.2165/00003088-198611040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Haemodialysis on the Pharmacokinetics and Haemodynamic Effects of Nifedipine During Continuous Intravenous Infusion

Abstract: The pharmacokinetics and haemodynamic effects of nifedipine were studied in 5 patients on long term haemodialysis. In addition, clearance of the drug on 2 different types of artificial kidneys were measured in vitro. Nifedipine was administered intravenously (1.3 mg/h) from 6 hours before starting haemodialysis to the end of haemodialysis, performed according to the standard protocol of each patient. Before and during haemodialysis, blood samples were taken for determination of free and total plasma nifedipine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…This discrepancy might be due to a specific effect of dihydropyridine on baroreflex function (Heesch et al, 1983) or to the higher reflex tachycardia ratio recorded in our work. It has been demonstrated that the speed of dihydropyridine intravenous administration greatly influences the degree of the tachycardia (Kleinbloesem et al, 1985). Our protocol created more marked stimulation of the sympathetic nervous system, and therefore facilitated demonstration of sympathetic inhibition after ACE inhibition.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy might be due to a specific effect of dihydropyridine on baroreflex function (Heesch et al, 1983) or to the higher reflex tachycardia ratio recorded in our work. It has been demonstrated that the speed of dihydropyridine intravenous administration greatly influences the degree of the tachycardia (Kleinbloesem et al, 1985). Our protocol created more marked stimulation of the sympathetic nervous system, and therefore facilitated demonstration of sympathetic inhibition after ACE inhibition.…”
Section: Discussionmentioning
confidence: 98%